Scramble Learning Model Assisted by Puzzle Media to Increase Motivation and Learning Outcomes of IPA Class V Students UPT SDN 286 Pinrang - Rosni, Rosni; Ismail, Ismail; S, Putriyani (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to improve students’ motivation and learning outcomes in Natural Science (IPA) subjects through the application of the Scramble learning model supported by puzzle media. The research was conducted in two cycles, each involving the stages of planning, implementation, observation, and reflection. In Cycle I, the average student motivation was recorded at a moderate level (3.25) and the average student test score was 72.83, indicating variations in student motivation and learning outcomes. Based on the observations, improvements were needed, so in Cycle II, the researcher introduced more group discussion activities and modified the puzzle to make it more challenging. The results from Cycle II showed significant improvement with the average student motivation rising to 4.8 and the average student test score increasing to 81.88. This increase shows that the Scramble learning model assisted by puzzle media is effective in increasing student motivation and learning outcomes. The well-designed puzzle media, as well as group discussion activities, contributed to increased student engagement and understanding of the subject matter. This study concludes that the implementation of strategies involving a variety of learning media and group collaboration can significantly improve students’ motivation and learning outcomes. The findings provide a strong basis for further development in learning practices and emphasize the importance of evaluation and adjustment of learning methods to achieve optimal results.